The well-being, peer cultures and rights of children - Bass, Loretta Elizabeth; Kinney, David A., 1960- (Sociological studies of children and youth ;, 2011)
This volume is comprised of empirical research and theoretical papers within three key areas, namely childrens well being, children and youth peer cultures, and the rights of children and youth. These empirical studies include childrens voices and experiences from four continents (Asia, Europe, North America and South America) and a range of methodological and theoretical orientations. A clear connection to social policy at a national and international level is made in many of these studies. Topics are wide-ranging and include: Praetorian militarization; school mobility; math and reading achievement gaps; dating and the developmental discourse in a summer camp; and school and social exclusion for urban young people. Altogether, these studies highlight how structure and culture both limit and enable the life chances of children, how children interpret and construct their social relations and environments, and how children view themselves as well as how others view the rights of children. This volume is a further example of how the Sociological Studies of Children and Youth series successfully showcases major strands of current thinking on children and youth in our world today.